2015
DOI: 10.5826/dpc.0504a13
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic findings in different clinical variants of lichen planus. Is dermoscopy useful?

Abstract: Lichen planus (LP) is a papulosquamous dermatosis that involves the skin, scalp, nails and mucous membranes. Although its pathogenesis is still unknown, there is evidence that an imbalance of immunologic cellular reactivity plays an important role. Histopathologic examination reveals characteristic interface dermatitis.Dermoscopy is a non-invasive tool, useful in the assessment of inflammatory dermatoses, such as lichen planus. In this paper we describe the dermoscopic findings of different variants of LP (ung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 9 publications
0
45
0
4
Order By: Relevance
“…However, epidemiological history, clinical presentation and dermoscopic findings pointed to the diagnosis of LPP, which was confirmed through histopathology [9,10]. …”
Section: Figmentioning
confidence: 99%
“…However, epidemiological history, clinical presentation and dermoscopic findings pointed to the diagnosis of LPP, which was confirmed through histopathology [9,10]. …”
Section: Figmentioning
confidence: 99%
“…Although its pathogenesis is still unknown, there is evidence that immunological mechanisms, infections, genetic predisposition, allergic reactions to drugs, psychogenic disorders and some chronic and endocrine diseases may play important roles [1,2]. It has been reported that LP shows cancerous characteristics, but its neoplastic transformation rate in skin is low; while oral LP increases the risk of squamous cell carcinoma [3,4], and the World Health Organization (WHO) has classified oral LP as "potentially malignant lesions" [5].…”
Section: Introductionmentioning
confidence: 99%
“…In cutaneous LP, WS most commonly present as white streaks in a reticular pattern, although other patterns have been reported including circular, radial streaming, linear, globular, veil-like, leaf venation, and starry sky/white dots 10, 13, 14 . In the current case, WS presented as – veil-like structureless grey-white to bluish white areas, and specked-pearly pattern in few foci.…”
Section: Discussionmentioning
confidence: 99%